Method for improving metal deposition effect of TGV glass substrate

By using an electrodeposition solution containing organic complexing agent, nanodispersant, corrosion inhibitor and surfactant during the metal deposition process of TGV glass substrate, and using pulse power, the problems of uneven deposition and easy cracks are solved, and a high-quality metal deposition layer is achieved to meet the needs of high-performance semiconductor devices.

CN119776935AInactive Publication Date: 2025-04-08SICHUAN SHUWANG CHENSHENG NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510086690.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing TGV glass substrate metal deposition technology has problems such as uneven deposition, concentrated stress and easy cracks, which affects the signal transmission quality and the reliability of the substrate.

Method used

Using an electrodeposition solution containing organic complexing agent, nanodispersant, corrosion inhibitor and surfactant, uniform metal deposition is achieved by adjusting the release rate of metal ions and the stress of the deposition layer, and pulsed power is used during the deposition process to reduce stress concentration.

Benefits of technology

The uniform metal deposition of the inner wall and surface of the through-hole of the glass substrate is achieved, which reduces the possibility of cracks, improves the comprehensive performance of the deposition layer and the reliability of the product, and is suitable for the needs of high-performance semiconductor devices.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for improving the metal deposition effect of a TGV glass substrate, and belongs to the technical field of glass. According to the technical scheme, an electro-deposition solution used for metal deposition comprises metal salt and additives, the additives comprise an organic complexing agent, a nano dispersing agent, a corrosion inhibitor and a surfactant, the organic complexing agent is at least one of tartaric acid, malic acid and ethylenediamine tetraacetic acid, the nano dispersing agent is nano titanium dioxide, the corrosion inhibitor is benzotriazole, and the surfactant is a surfactant. The surfactant is lauryl sodium sulfate. The problems that in the prior art, deposition is not uniform, cracks are prone to being generated and the like are solved, and the deposition efficiency and the comprehensive performance of a deposition layer are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field, and in particular to a method for improving metal deposition effect on a TGV glass substrate. Background Art

[0002] As a cutting-edge technology in the field of electronic packaging, TGV technology has occupied a place in the electronic manufacturing industry with its unique advantages. This technology forms tiny through holes on the glass substrate to achieve smooth transmission of electrical signals, thereby significantly improving the integration and performance of the circuit.

[0003] Alkali-free glass substrates are widely used in TGV technology due to their excellent physical and chemical properties, such as high thermal stability, low thermal expansion coefficient, and good electrical insulation. However, the brittleness of alkali-free glass makes it easy to crack during through-hole processing, affecting the integrity and reliability of the substrate. In addition, the poor interface compatibility between alkali-free glass and metal materials makes it extremely difficult to achieve uniform, crack-free metal filling in high aspect ratio through-holes.

[0004] Traditional metal deposition methods have the following limitations: 1) Uneven deposition: Traditional metal deposition methods often have difficulty achieving a uniform metal layer, resulting in uneven metal thickness in the through-hole, affecting the quality of signal transmission; 2) Stress concentration: The stress concentration generated during the metal deposition process can easily lead to cracks in the substrate, and in severe cases can even cause the substrate to break; 3) Crack generation: Due to uneven deposition and stress concentration, cracks are easily generated in the metal layer in the through-hole, affecting the connectivity and reliability of the circuit, making it difficult to meet the growing demand for high-performance semiconductor devices. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for improving the metal deposition effect of a TGV glass substrate, so as to solve the problems of uneven deposition and easy generation of cracks in the prior art, and further improve the deposition efficiency and the comprehensive performance of the deposited layer.

[0006] The technical solution of the present invention is:

[0007] The invention discloses a method for improving the metal deposition effect of a TGV glass substrate. The electroplating solution used for metal deposition comprises a metal salt and an additive. The additive comprises an organic complexing agent, a nano-dispersant, a corrosion inhibitor and a surfactant. The organic complexing agent is at least one of tartaric acid, malic acid and ethylenediaminetetraacetic acid, the nano-dispersant is nano-titanium dioxide, the corrosion inhibitor is benzotriazole, and the surfactant is sodium dodecyl sulfate.

[0008] In the present invention, the organic complexing agent can form a stable complex with the metal ions, and the release rate of the metal ions can be effectively controlled by adjusting the amount of addition, thereby helping to achieve more uniform metal deposition, and can better adjust the stress of the deposited layer to avoid cracks caused by stress concentration. The addition of a surfactant can reduce the surface tension of the solution, promote the diffusion of metal ions in the through-hole, and further improve the uniformity of deposition. The nano-dispersant can evenly disperse the metal ions and additives in the solution, prevent agglomeration, and ensure the stability of the deposition process. The corrosion inhibitor can form a protective film on the surface of the glass substrate, reduce the corrosion of the substrate during the metal deposition process, and improve the reliability of the product. In the process of metal deposition, since the complex formed by the additive and the metal ions continuously and stably releases the metal ions, it is ensured that the inner wall and the surface of the through-hole of the glass substrate can obtain uniform metal deposition, and the stress of the deposited layer is well adjusted, and finally a high-quality metal deposition layer is obtained to meet the high-performance requirements of TGV.

[0009] Preferably, the molar ratio of the organic complexing agent to the metal salt is (0.05-0.2):1.

[0010] Preferably, the concentration of the nanodispersant is 0.1-0.5 g / L.

[0011] Preferably, the concentration of the corrosion inhibitor is 0.02-0.1 mol / L.

[0012] Preferably, the concentration of the surfactant is 0.01-0.05 g / L.

[0013] Preferably, the metal salt is copper sulfate, nickel sulfate or silver nitrate.

[0014] Preferably, the method specifically comprises the following steps:

[0015] S1: preparing an electrodeposition solution containing a metal salt by using a metal salt, an organic complexing agent, a nanodispersant, a corrosion inhibitor and a surfactant, and stirring the solution uniformly;

[0016] S2: immerse the pre-treated TGV glass substrate into the electrodeposition solution prepared in step S2 to perform metal deposition. The current density during deposition is 1.5-3A / dm 2 The deposition temperature is 25-40°C, the deposition time is 20-50min, and a pulse power supply is used, the pulse frequency is 50-200Hz, and the duty cycle is 30-70%.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. The present invention adds an organic complexing agent, a nano-dispersant, a corrosion inhibitor and a surfactant to the electrodeposition solution. The additives work synergistically to make the metal ions evenly deposited on the glass substrate, avoid uneven local deposition, ensure uniform deposition on the through-holes and surface of the TGV substrate, and improve the quality. At the same time, the additives can adjust the stress of the deposited layer, disperse the stress to prevent concentration, reduce the possibility of cracks from the root, and finally prove that the method of the present invention is adopted, and there are no obvious cracks in the deposited layers of copper, nickel, silver, etc., ensuring that the TGV product structure is complete and reliable, and adapting to the subsequent semiconductor packaging process.

[0019] 2. The present invention reduces concentration polarization by adopting a pulse power supply and optimized deposition parameters, thereby improving deposition efficiency, shortening production cycle, and reducing production costs while ensuring deposition quality.

[0020] 3. The present invention solves the problems of metal deposition, cracks and corrosion, greatly increases the yield rate, can stably produce high-quality substrates, broaden semiconductor manufacturing applications, and provide reliable substrates for device packaging. DETAILED DESCRIPTION

[0021] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0022] Example 1

[0023] The method of improving the metal deposition effect of the TGV glass substrate of this embodiment includes the following steps:

[0024] S1: preparing an electrodeposition solution containing metal salts: adding 80 g of copper sulfate, 7.5 g of tartaric acid, 0.1 g of nano titanium dioxide dispersant, 2.38 g of benzotriazole and 0.01 g of sodium dodecyl sulfate to 0.5 L of pure water, stirring and dissolving, and then adjusting the volume to 1 L;

[0025] S2 puts the cleaned TGV glass substrate into the solution tank of the electrodeposition device, with the copper plate as the anode and the glass substrate as the cathode, and sets the current density to 2A / dm 2 , the deposition temperature is 30°C, the deposition time is 30 min, a pulse power supply is used, the pulse frequency is 100 Hz, and the duty cycle is 50%.

[0026] After the deposition was completed, the glass substrate was taken out and tested to find that the copper deposition layer had good uniformity, no obvious defects in the through-holes, the stress of the deposition layer was significantly reduced, no cracks appeared, and the deposition efficiency was improved compared to traditional DC power deposition. There was no obvious sign of corrosion on the substrate surface.

[0027] Example 2

[0028] The method of improving the metal deposition effect of the TGV glass substrate of this embodiment includes the following steps:

[0029] S1: preparing an electrodeposition solution containing metal salts: adding 128 g of copper sulfate, 13.9 g of malic acid, 0.3 g of nano titanium dioxide dispersant, 5.95 g of benzotriazole and 0.03 g of sodium dodecyl sulfate to 0.5 L of pure water, stirring and dissolving, and then adjusting the volume to 1 L;

[0030] S2 puts the cleaned TGV glass substrate into the solution tank of the electrodeposition device, with the copper plate as the anode and the glass substrate as the cathode, and sets the current density to 2.5A / dm 2 , the deposition temperature is 30°C, the deposition time is 40 min, a pulse power supply is used, the pulse frequency is 150 Hz, and the duty cycle is 40%.

[0031] After the deposition was completed, the glass substrate was taken out and tested to find that the copper deposition layer had good uniformity, no obvious defects in the through-holes, the stress of the deposition layer was significantly reduced, no cracks appeared, and the deposition efficiency was improved compared to traditional DC power deposition. There was no obvious sign of corrosion on the substrate surface.

[0032] Example 3

[0033] The method of improving the metal deposition effect of the TGV glass substrate of this embodiment includes the following steps:

[0034] S1: preparing an electrodeposition solution containing metal salts: adding 93 g nickel sulfate, 18 g tartaric acid, 0.2 g nano titanium dioxide dispersant, 3.57 g benzotriazole and 0.02 g sodium dodecyl sulfate to 0.5 L pure water, stirring and dissolving, and then adjusting the volume to 1 L;

[0035] S2 puts the cleaned TGV glass substrate into the solution tank of the electrodeposition device, with the nickel plate as the anode and the glass substrate as the cathode, and sets the current density to 1.5A / dm 2 The deposition temperature is 35°C, the deposition time is 35 min, a pulse power supply is used, the pulse frequency is 80 Hz, and the duty cycle is 60%.

[0036] After the deposition was completed, the glass substrate was taken out and tested to find that the nickel deposition layer had good uniformity, no obvious defects in the through-holes, the stress of the deposition layer was significantly reduced, no cracks appeared, and the deposition efficiency was improved compared to traditional DC power deposition. There was no obvious sign of corrosion on the substrate surface.

[0037] Example 4

[0038] The method of improving the metal deposition effect of the TGV glass substrate of this embodiment includes the following steps:

[0039] S1: preparing an electrodeposition solution containing metal salts: adding 128 g of copper sulfate, 29.2 g of ethylenediaminetetraacetic acid, 0.4 g of nano titanium dioxide dispersant, 8.33 g of benzotriazole and 0.04 g of sodium dodecyl sulfate to 0.5 L of pure water, stirring and dissolving, and then adjusting the volume to 1 L;

[0040] S2 puts the cleaned TGV glass substrate into the solution tank of the electrodeposition device, with the copper plate as the anode and the glass substrate as the cathode, and sets the current density to 2.2A / dm 2 The deposition temperature is 32°C, the deposition time is 32 min, a pulse power supply is used, the pulse frequency is 120 Hz, and the duty cycle is 55%.

[0041] After the deposition was completed, the glass substrate was taken out and tested to find that the copper deposition layer had good uniformity, no obvious defects in the through-holes, the stress of the deposition layer was significantly reduced, no cracks appeared, and the deposition efficiency was improved compared to traditional DC power deposition. There was no obvious sign of corrosion on the substrate surface.

[0042] Example 5

[0043] The method of improving the metal deposition effect of the TGV glass substrate of this embodiment includes the following steps:

[0044] S1: preparing an electrodeposition solution containing metal salts: adding 68 g of silver nitrate, 9.38 g of malic acid, 0.15 g of nano titanium dioxide dispersant, 2.975 g of benzotriazole and 0.015 g of sodium dodecyl sulfate to 0.5 L of pure water, stirring and dissolving, and then adjusting the volume to 1 L;

[0045] S2 puts the cleaned TGV glass substrate into the solution tank of the electrodeposition device, with the copper plate as the anode and the glass substrate as the cathode, and sets the current density to 1.8A / dm 2 The deposition temperature is 28°C, the deposition time is 25 min, a pulse power supply is used, the pulse frequency is 60 Hz, and the duty cycle is 70%.

[0046] After the deposition was completed, the glass substrate was taken out and tested to find that the silver deposition layer had good uniformity, no obvious defects in the through-holes, the stress of the deposition layer was significantly reduced, no cracks appeared, and the deposition efficiency was improved compared to traditional DC power deposition. There was no obvious sign of corrosion on the substrate surface.

[0047] Comparative Example 1

[0048] The difference from Example 1 is that in step S1, when preparing the electrodeposition solution containing the metal salt, no additive is added.

[0049] After the deposition is completed, the glass substrate is taken out. It is found that the thickness of the copper deposition layer is uneven, thicker accumulation occurs locally, and the deposition in some areas is too thin, and there are obvious cracks, which cannot meet the use requirements. The deposition efficiency is also low, and the substrate has obvious corrosion marks. This is because the behavior of metal ions in the solution is difficult to be effectively regulated in the absence of additives. First, due to the lack of organic complexing agents, it is impossible to form a stable complex with metal ions to control their release rate, resulting in a large number of metal ions deposited quickly in certain areas during the deposition process, while other areas are too thin due to insufficient ion supply, resulting in uneven deposition. Secondly, due to the lack of nano-dispersants, metal ions and possible impurities in the solution are easy to agglomerate, further affecting the uniformity and stability of the deposition, resulting in the formation of thicker accumulation locally. Furthermore, due to the lack of corrosion inhibitor benzotriazole, a protective film cannot be formed on the surface of the glass substrate during metal deposition. The metal will directly react with the substrate, causing the substrate to be corroded, and also affecting the bonding force between the deposition layer and the substrate, exacerbating the generation of cracks. Finally, there is no surfactant to reduce the surface tension of the solution, and the diffusion of metal ions in the through hole is hindered, which is not conducive to uniform deposition. The combination of the above factors led to the final adverse result.

[0050] Comparative Example 2

[0051] The difference from Example 2 is that in step S1, when preparing the electrodeposition solution containing the metal salt, malic acid is not added.

[0052] After the deposition is completed, the glass substrate is taken out. It is found through testing that the copper deposition layer has poor uniformity, and there are many cases of uneven thickness. The metal deposition is thicker in some areas and thinner in some areas. Similar problems also exist in the through-holes, and a small amount of cracks are generated. This is because Comparative Example 2 lacks an organic complexing agent such as malic acid, and cannot effectively form a stable complex with metal ions to adjust the metal ion release rate, resulting in the metal ions not being able to evenly reach the glass substrate for deposition during the deposition process, thereby causing uneven deposition. At the same time, since the stress of the deposited layer cannot be well adjusted, the stress concentration phenomenon is more obvious, and cracks are generated. The deposition efficiency is also reduced, and there are signs of corrosion to a certain extent on the surface of the substrate.

[0053] Comparative Example 3

[0054] The difference from Example 2 is that in step S1, when preparing the electrodeposition solution containing the metal salt, the added amount of malic acid is 40.2 g.

[0055] After the deposition is completed, the glass substrate is taken out and tested to find that too much organic chelating agent will excessively bind the metal ions, causing the metal ions to be released too slowly, greatly reducing the deposition efficiency and being unable to meet the needs of industrial production. In addition, excess organic chelating agent may remain in the deposited layer, affecting the purity and electrical properties of the deposited layer, failing to meet product standards, and the substrate is corroded.

[0056] Comparative Example 4

[0057] The difference from Example 2 is that in step S1, when preparing the electrodeposition solution containing the metal salt, the added amount of malic acid is 2.65 g.

[0058] After the deposition is completed, the glass substrate is taken out and tested to find that the amount of organic chelating agent added is too small, the number of complexes formed is limited, and it is difficult to fully control the metal ion release rate, which will lead to the rapid release of metal ions in the initial stage of deposition, resulting in uneven deposition, forming a thicker deposition layer in local areas of the substrate, while other areas are insufficiently deposited and the stress concentration phenomenon is serious; at the same time, it is impossible to effectively adjust the stress of the deposited layer, cracks appear in many places, the product is unqualified, the deposition efficiency is poor, and the substrate is severely corroded.

[0059] Comparative Example 5

[0060] The difference from Example 3 is that in step S1, when preparing the electrodeposition solution containing the metal salt, no nano titanium dioxide dispersant is added.

[0061] After the deposition is completed, the glass substrate is taken out and it is found through testing that the uniformity of the deposited layer has deteriorated significantly. The metal ions and additives in the solution have agglomerated, resulting in uneven deposition on the glass substrate, local metal accumulation, and insufficient metal coverage in some areas. In the through-holes, this unevenness is more prominent and more cracks are generated. This is because the metal ions and additives in the solution cannot be evenly dispersed without adding nano-titanium dioxide dispersant, making the deposition process unstable and affecting the final deposition effect; the deposition efficiency is reduced, and there is corrosion on the substrate surface.

[0062] Comparative Example 6

[0063] The difference from Example 1 is that in step S1, when preparing the electrodeposition solution containing the metal salt, no benzotriazole is added.

[0064] After the deposition was completed, the glass substrate was taken out. It was found through testing that although the copper deposition layer had no serious problems in terms of uniformity, there were obvious corrosion marks on the surface of the substrate, and some tiny defects appeared at the interface between the deposition layer and the glass substrate. This is because the lack of benzotriazole, a corrosion inhibitor, made it impossible to form an effective protective film on the surface of the glass substrate during the metal deposition process, which caused the metal to corrode the substrate, affecting the reliability of the product; the deposition efficiency was slightly lower than that of Example 1.

[0065] Comparative Example 7

[0066] The difference from Example 1 is that in step S2, a conventional DC power supply is used for deposition, and the current density is 2A / dm 2 , the deposition temperature is 30℃, and the deposition time is 80min.

[0067] After the deposition was completed, the glass substrate was taken out and it was found through testing that although the uniformity and crack conditions of the copper deposition layer were similar to those in Example 1, the deposition time was significantly prolonged and the deposition efficiency was lower than that in Example 1; and the substrate was corroded to a certain extent, indicating that the pulse power supply plays an important role in improving the deposition efficiency and preventing the corrosion of the substrate.

[0068] Through the above embodiments and comparative examples, the effectiveness and feasibility of the method for improving the metal deposition effect of TGV glass substrate proposed in the present invention are verified, which can provide reliable technical support for the semiconductor packaging industry and improve the quality of TGV products.

Claims

1. A method for improving the metal deposition effect of a TGV glass substrate, characterized in that: The electrodeposition solution used for metal deposition includes metal salt and additives, wherein the additives include organic complexing agent, nano-dispersant, corrosion inhibitor and surfactant, wherein the organic complexing agent is at least one of tartaric acid, malic acid and ethylenediaminetetraacetic acid, the nano-dispersant is nano-titanium dioxide, the corrosion inhibitor is benzotriazole, and the surfactant is sodium dodecyl sulfate.

2. The method for improving metal deposition effect on TGV glass substrate according to claim 1, characterized in that: The molar ratio of the organic complexing agent to the metal salt is (0.05-0.2):

1.

3. The method for improving metal deposition effect on TGV glass substrate according to claim 1, characterized in that: The concentration of the nano-dispersant is 0.1-0.5 g / L.

4. The method for improving metal deposition effect on TGV glass substrate according to claim 1, characterized in that: The concentration of the corrosion inhibitor is 0.02-0.1 mol / L.

5. The method for improving metal deposition effect on TGV glass substrate according to claim 1, characterized in that: The concentration of the surfactant is 0.01-0.05 g / L.

6. The method for improving metal deposition effect on TGV glass substrate according to claim 1, characterized in that: The metal salt is copper sulfate, nickel sulfate or silver nitrate.

7. The method for improving metal deposition effect on TGV glass substrate according to claim 1, characterized in that: The specific steps include: S1: preparing an electrodeposition solution containing a metal salt by using a metal salt, an organic complexing agent, a nanodispersant, a corrosion inhibitor and a surfactant, and stirring the solution uniformly; S2: immerse the pre-treated TGV glass substrate into the electrodeposition solution prepared in step S2 to perform metal deposition. The current density during deposition is 1.5-3A / dm 2 The deposition temperature is 25-40°C, the deposition time is 20-50min, and a pulse power supply is used, the pulse frequency is 50-200Hz, and the duty cycle is 30-70%.

Citation Information

Patent Citations

  • Pulse electrodeposition nickel-iron plating process for wear-resistant and corrosion-resistant surface of aluminum or aluminum-silicon alloy

    CN119020835A

  • Process for electroplating silicon wafers

    US20030155247A1

  • Process for electroless copper deposition

    US20070099422A1

  • Method for continuous metal deposition from a non-autocatalytic electroless plating bath using electric potential

    US4459184A